Evaluations of knowledge, skills and practices of insulin storage and injection handling techniques of diabetic patients in Ethiopian primary hospitals - Adeladlew Kassie Netere; Eyayaw Ashete; Eyob Alemayehu Gebreyohannes; Sewunet Admasu Belachew (BMC, 2020)
Abstract Background Insulin is an effective therapeutic agent in the management of diabetes, but also sensitive to the external environment. Consequently, diabetic patients' adherence to insulin delivery recommendations is critical for better effectiveness. Patients' lack of knowledge, skill and irrational practices towards appropriate insulin delivery techniques may end up in therapeutic failure and increase costs of therapy. The aim of this study was to evaluate patients' knowledge, skills and practices of insulin storage and injection techniques. Methods An interview-based cross-sectional study was conducted through purposive selection of participants in Northwest Ethiopian primary hospitals from March 1 to May 30, 2019. Levels of knowledge were assessed with right or wrong responses, while practice was measured by using a 4-point Likert scale structured questionnaire collected via face-to-face interviews. Likewise, a five-point observational (demonstration) techniques checklist employed to assess patients' skills. Results Among 194 patients approached, 166 participants completed the survey giving a response rate of 85.6%. More than half of the respondents (54.8%) were males and the mean age (±SD) was 38.5 ± 13.8 years. The overall patients' median knowledge and practice levels on insulin storage and handling techniques were moderately adequate (64.3%) and fair (55.4%), respectively. In patients' skill assessments, 94.6% correctly showed injection sites, 70% indicated injection site rotations, and 60.75% practiced injection site rotations. Education (P < 0.001), duration of insulin therapy (P = 0.008), and duration of diabetes (P = 0.014) had significant impact on knowledge level. Education (P < 0.001), occupation (P < 0.001), duration of insulin therapy (P = 0.001), duration of diabetes (P = 0.036) and patients' knowledge level (P < 0.001) were found to have a significant effects on the patients' practice levels. A Mann-Whitney U test also disclosed that residency, ways to get insulin and mocked injection technique during the first training had significant effects on patients' knowledge levels. Conclusion The current study revealed that patients had moderately adequate knowledge and fair practice levels on insulin storage and handling techniques. However, patients missed important insulin administration skills. This study highlights the need of regular public health education so as to enhance the patients' knowledge, skill and practice levels on insulin handling techniques.